RETRACTED: Leishmania-Specific Promiscuous Membrane Protein Tubulin Folding Cofactor D Divulges Th1/Th2 Polarization in the Host via ERK-1/2 and p38 MAPK Signaling Cascade - Jamal, Fauzia; Singh, Manish K.; Hansa, Jagadish; Pushpanjali,; Ahmad, Ghufran; Dikhit, Manas Ranjan; Umar, Mohd Saad; Bimal, Sanjiva; Das, Pradeep; Mujeeb, Anzar Abdul; Singh, Shubhankar K.; Zubair, Swaleha; et al. (Frontiers in Immunology, 2020)
Visceral leishmaniasis (VL) related mortality and morbidity imposes a great deal of health hazard across the globe. The existing anti-leishmanial drug regimen generally fails to eliminate newly emerging resistant isolates of this dreadful parasite.In such circumstances, development of a prophylactic strategy to impart protection against the disease is likely to take a center stage. In order to develop a promising prophylactic vaccine, it is desirable to identify an adequately potential vaccine candidate.In silico analysis of Leishmania tubulin folding cofactor D protein predicted its potential to activate both B and T cell repertoires. Furthermore, the ELISA employing anti-Peptide27 (a segment of tubulin folding cofactor D) antibody revealed its proficiency in VL diagnosis and treatment monitoring. Coherent to the consequence of peptide specific humoral immune response, the prophylactic ability of the peptide27 and its cocktail with peptide23 has been assessed against VL in BALB/c mice.The cocktail-based vaccine prompted up-regulation of Th1 cytokines viz. IFN-γ, TNF-α, IL-17 and IL-2 and down-regulation of immune-regulatory cytokine such as IL-10. The peptide cocktail-based immunization ensued in elicitation of pathogen specific humoral response with predominant amplification of IgG2a over IgG1 isotype, up-regulated proliferation of T lymphocytes and enhanced production of nitric oxide (NO) and reactive oxygen species (ROS). The peptide cocktail mediated activation of host immune armory eventually translated into significant decline in parasitic load in visceral organs of experimental animals challenged with Leishmania donovani. Finally, it was established that implied immunization protocol modulated host MAPK signaling to favor amplification of Th1 dominated immune response in the host. The elicited Th1 dominant immune response imparted impressive protection against experimental VL in the immunized animals.